Persepsi Pekerja Terhadap Perlaksanaan Sistem Pengurusan Kualiti MS ISO 9000 : Kajian Kes di Modenas - Rina Illyana, Kasa @ Halim (2004)
Quality management has had considerable success in terms of its acceptance in organizational worldwide. Quality management is one of the most talked about areas for research and teaching. Due to its short history, however there is still much confusion surrounding the effect f ISO 9000:1994 registration. Nowadays, there have been numbers of organization that has been certified with ISO 9000: 1994 certification but the management system is still the same as well as the quality of product offered to the customer. This research has been conducted to know the worker's perception toward the ISO 9000:1994 implementation and the product's quality that offered to the customer whether the quality is still the same or it has been improved. This research has been conducted in Motosikal dan Enjin Nasional Sdn. Bhd and well known as Modenas, which is located in Gurun, Kedah. The whole numbers of workers has been selected as respondent, which are 250 workers all together. The sample for this research is population. Finds that workers have good perception toward the ISO 9000:1994 implementations and worker's view of the organization's product quality has been increased.